1984
DOI: 10.1172/jci111233
|View full text |Cite
|
Sign up to set email alerts
|

Role of iron in Trypanosoma cruzi infection of mice.

Abstract: As bstract. The role of iron in experimental infection of mice with Trypanosoma cruzi was investigated. B6 mice had a transient parasitemia and a transient anemia, both of maximal intensity 28 d after the inoculation of T. cruzi. There was a biphasic hypoferremic host response to infection with T. cruzi with the peak hypoferremia also occurring 28 d after inoculation ofthe parasite. The mortality rate from infection was increased from 23% in phosphate-buffered saline-treated B6 mice to 50% in a group of B6 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 14 publications
7
62
0
Order By: Relevance
“…cruzi amastigotes require iron to grow in axenic cultures (57). Chelating iron reduces T. cruzi infection in macrophages (58) and mice (59), while iron-rich diets or iron-dextran worsen infection (60), suggesting that iron is critical for T. cruzi growth. Here, we found that several strategies to increase the labile iron pool resulted in increased parasitism, while incubation of infected macrophages with Fe 2+ reversed the decrease in parasitism mediated by CoPP and other antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…cruzi amastigotes require iron to grow in axenic cultures (57). Chelating iron reduces T. cruzi infection in macrophages (58) and mice (59), while iron-rich diets or iron-dextran worsen infection (60), suggesting that iron is critical for T. cruzi growth. Here, we found that several strategies to increase the labile iron pool resulted in increased parasitism, while incubation of infected macrophages with Fe 2+ reversed the decrease in parasitism mediated by CoPP and other antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, T. cruzi-infected mice fed iron dextran to increase intracellular iron stores have an increased mortality rate. Conversely, depletion of host iron stores with desferroxamine and an iron-deficient diet reduce the pathogenicity of infection with T. cruzi (46).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of these cytokines is increased in a variety of infectious and noninfectious states, and these cytokines are felt to play a role in the hypoferremia seen in sepsis and chronic disease (35)(36)(37)(38). In the host infected with certain intracellular pathogens, this effect of IL-1 and TNF-increasing mononuclear phagocyte iron and ferritin may be detrimental (39). IFNy, a cytokine more specific to the cell-mediated immune response against intracellular pathogens, may play an important role in counteracting the influence of IL-1 and TNF on iron metabolism in mononuclear phagocytes.…”
Section: Discussionmentioning
confidence: 99%